Nurses as communicator in a caring profession - Wan Su, Kamaruzaman (2010)
Medical and nursing are both caring professions which need the practitioners to indulge in effective communication with their clients. They are dealing with people who are in need of help both physically and emotionally. If the medical doctors are engaged in treating the patients, the nurses are the team members who carry out the orders and take charge of caring the patients around the clock. They have to work as a team, understand each other's role and help each other for the benefit of the clients. Besides communicating with the clients, nurses are also communicating with the members of the team which include the doctors, their superiors and the other allied health practitioners. Failure in this communication will lead to ineffective patient-care, unsatisfactory feeling ofthe clients and even litigation in courts. Nurses with effective communication skills can end up with good job satisfaction and less stress in work. Communication itself is therapeutic. If nurses can communicate and feel what the patients feel (empathy), half of the problem suffered by the patients will be solved. But however, in the advent of modern information technologies and modern medical technologies, less and less nurses engage in effective communication with their clients and team members. This can be evidenced from more and more reports of patient's dissatisfaction and medico-legal cases appearing in courts. Most of these medico-legal cases arise from failure in communication and not due to real medical negligence. In this paper, the author will attempt to analyze some of the barriers in communication faced by nurses based on research in literature review and also based on his experience as a doctor working with the nurses.